Inovasi Pelayanan Kesehatan Melalui Program Rumah Singgah Pasien Dan Keluarga Pada Dinas Kesehatan Kabupaten Sinjai (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
Abstract  This study aimed to analyze the application of Health Service Innovation through the Shelter Patient and Family Program in improving quality health service in Sinjai Regency using best practice theory according to United Nations (UN). This study used qualitative methods with the type of research phenomenology. Data analysis techniques were data reduction steps, data presentation, and conclusion. The results of this study showed that health service innovation through the halfway house program for patients and families at the Sinjai Regency Health Office had not fully implemented according to best practice criteria. There were still some indicators had not icarried out optimally. This could be seen from the indicators (1) Impact, (2) Partnership, (3) Sustainability, (4) Community Leadership and Empowerment, (5) Gender Equality and Social Exclusion and (6) Innovation in Local and Transferable Contexts. Key Words: Innovation, Service, Health, Halfway House